2g+3(-7+2g)=1-9

Simple and best practice solution for 2g+3(-7+2g)=1-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2g+3(-7+2g)=1-9 equation:


Simplifying
2g + 3(-7 + 2g) = 1 + -9
2g + (-7 * 3 + 2g * 3) = 1 + -9
2g + (-21 + 6g) = 1 + -9

Reorder the terms:
-21 + 2g + 6g = 1 + -9

Combine like terms: 2g + 6g = 8g
-21 + 8g = 1 + -9

Combine like terms: 1 + -9 = -8
-21 + 8g = -8

Solving
-21 + 8g = -8

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '21' to each side of the equation.
-21 + 21 + 8g = -8 + 21

Combine like terms: -21 + 21 = 0
0 + 8g = -8 + 21
8g = -8 + 21

Combine like terms: -8 + 21 = 13
8g = 13

Divide each side by '8'.
g = 1.625

Simplifying
g = 1.625

See similar equations:

| .50x+.35(70)=44.5 | | 125+13x=21 | | -2y+6=y^2-9 | | 5(2)+2=10 | | -(3x+3)-2(3y+3)= | | 7a^3+22a^2+3a=0 | | 7(5x-2)=7(4x+6) | | x(9)=54 | | -x-2=12x | | 6n-5n+4n=20 | | -6a-6a=24 | | 2(x+8)-6x=-2(x-3) | | 1.4(z+0.5)=0.7(z-1.3) | | -2-13.8n=-8-(6n+1) | | -4y-16=2x | | 15=3over | | m+11=1 | | -11y+32=104-5t | | 90+90+x+x+x+x=180 | | 12.3=9.4+a | | 26=pi*d | | -6.6x+11+1.3+2x= | | -14+s=6 | | 2(2k*1)=4(k*2) | | 3x+18=5x+20 | | -5(7p-1)-(1+2p)=3+8p+1 | | -11+r=5 | | 8x-2x+5x= | | 4a+2a-3a=9 | | 13b-39=2 | | 67=-8+5x | | 8.2+1.6x=x+20.7 |

Equations solver categories